Analysis of mechanical energy in thigh, calf and foot during gait in children with cerebral palsy. (July 2022) - Hua, Wei; Nasir, Sadiq; Arnold, Graham; Wang, Weijie
Highlights: The mechanical energy changes of the thigh, calf and foot during gait were analysed. The children with cerebral palsy and typically developing were compared. The energy recovery in thigh in CP was 31% compared with 43% in the TD group. Both kinetic and potential energies were higher in TD than in CP during gait. Abstract: Background: Many studies on children with cerebral palsy (CP) have focused on metabolic energy, however research on the mechanical energy in the lower limbs is sparse. Research question: What differences of mechanical energies in the lower limbs exist between the children with CP and typically developing (TD) children during gait? The purpose of this research was to analyse the mechanical energy changes of the lower limbs of children with CP during walking and compare them with TD children. Methods: Twelve children with CP including 8 diplegic and 4 hemiplegic without severity levels (aged 4–22 year old) and 14 TD participants (aged 5–15 year old) walked barefoot in a gait lab where a motion capture system collected marker data during walking. The translational and rotative kinetic energy and potential energy in the thigh, calf and foot were then calculated using the marker data. Gait parameters, e.g., stride frequency, pace, stride length, stride width, were also obtained. Findings: The results show that the children with CP had significantly lower values than the TD group in terms of kinetic energy and potential energy. This was especially seen in the thigh where the energy recovery coefficient in the children with CP was 31% compared with 43% in the TD group. In the calf and foot, the CP and TD groups had similar energy recovery to the TD group, i.e. not significantly different clinically. The gait parameters showed that children with CP had slower walking speed, shorter stride length, larger step width than TD but similar cadence to TD. Interpretation: The energy recovery coefficient represents the efficiency of exchanges of kinetic and potential energies. The higher its value, the better the energy use during gait. Significance: This study concluded that CP gait is weaker in the use of energy than TD gait. To our best knowledge, this study is the first one to analyse mechanical energy changes in the lower limbs for CP and TD groups during gait.